An all-inorganic flexible and breathable SiO2@SnO2 needle-shaped fiber membrane gas sensitive material and a preparation method thereof

CN118256875BActive Publication Date: 2026-10-27SHAANXI NORMAL UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410399128.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-04-03
Publication Date
2026-10-27
Estimated Expiration
2044-04-03

AI Technical Summary

Technical Problem

然而,传统的基于有机基底的MOS柔性气体传感器还存在以下诸多不足:(1)有机基底和MOS材料往往通过单一界面进行结合,两者之间的结合力低;同时MOS材料具有高的刚度和脆性,因此传感器在柔性弯曲过程容易导致有机基底和MOS材料分离,进而导致传感器失效

Benefits of technology

[0016]1、本发明SiO2@SnO2松针状纤维膜由SiO2纳米纤维和SnO2纳米线组成,SiO2纳米纤维和SnO2纳米线相互交织成网络结构,一方面SiO2纳米纤维作为骨架材料具有良好的柔性;另一方面SnO2纳米线在非晶SiO2纳米纤维表面生长密集构成类似松针状的分级纳米结构,在弯曲状态下,产生的弯曲应力主要集中于SiO2纤维中,弯曲界面处垂直于界面生长的SnO2纳米线仅承受较小的应力,而非弯曲界面处的SnO2纳米线几乎不受应力的作用,并且细小的SnO2纳米线在受到应力后,可发生轻微的变形,避免应力的集中;此外纤维膜中的SnO2纳米线具有更细的直径,相较SnO2纳米纤维而言具有更好的柔性;因此本发明SiO2@SnO2松针状纤维膜表现出良好的柔性和结构稳定性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118256875B_ABST
    Figure CN118256875B_ABST
Patent Text Reader

Abstract

The application discloses a kind of all-inorganic flexible breathable SiO2@SnO2 pine needle-shaped fiber membrane gas sensitive materials and preparation method thereof, first electrostatic spinning method is used to prepare Si electrospinning fiber membrane;By high temperature calcination to Si electrospinning fiber membrane, get the amorphous SiO2 nanofiber membrane of very good flexibility;Then a thin Au film is deposited on the surface of amorphous SiO2 nanofiber membrane using ion sputtering method;Again, similar pine needle-shaped SnO2 nanowire is grown on the surface of amorphous SiO2 nanofiber by chemical vapor deposition method, and all-inorganic SiO2@SnO2 pine needle-shaped fiber membrane with high flexibility, high breathability and high temperature resistance characteristics is obtained. After plating electrode on its surface, all-inorganic flexible breathable SiO2@SnO2 fiber membrane gas sensor can be prepared, and the gas sensor shows excellent flexibility, high temperature resistance and room temperature NO2 sensitive performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of flexible gas sensor technology, specifically relating to a high-temperature resistant, highly flexible, highly permeable, and gas-sensitive all-inorganic flexible permeable SiO2@SnO2 needle-like fiber membrane material and its preparation method. Background Technology

[0002] Resistive switching metal-oxide-semiconductor (MOS) gas sensors have advantages such as low cost, high sensitivity, short response / recovery time, and good stability, and are currently widely studied gas sensors. The development of flexible electronics and the extensive application of various sensors in the Internet of Things have provided a broad market for gas sensors, while also placing higher demands on the portability and flexibility of sensors, especially requiring gas sensors to have better flexibility to meet the emerging needs of the wearable electronics field. However, traditional organic substrate-based MOS flexible gas sensors still have the following shortcomings: (1) Organic substrates and MOS materials are often bonded through a single interface, and the bonding force between the two is low; at the same time, MOS materials have high stiffness and brittleness, so the organic substrate and MOS materials are prone to separation during flexible bending, which leads to sensor failure. (2) In high-temperature environments, on the one hand, the organic substrate may undergo glass transition, leading to sensor failure; on the other hand, the thermal expansion coefficients of the organic substrate and MOS materials are very different, which may lead to separation of the organic substrate and MOS materials, leading to sensor failure, which seriously affects the application of MOS flexible gas sensors in high-temperature fields. (3) The room temperature gas sensing performance of the reported flexible gases is generally low, and the gas sensing performance needs to be further improved. Therefore, developing a flexible MOS gas sensor with good flexibility, heat resistance and high gas sensitivity remains an urgent problem to be solved. Summary of the Invention

[0003] To overcome the technical shortcomings of existing flexible gas sensors, this invention provides a high-temperature resistant, highly flexible, gas-sensitive, all-inorganic flexible breathable SiO2@SnO2 needle-like fiber membrane gas-sensitive material and its preparation method.

[0004] The all-inorganic flexible breathable SiO2@SnO2 pine needle-like fiber membrane gas-sensitive material provided by this invention is prepared by the following method:

[0005] Step 1: Mix distilled water, tetraethyl orthosilicate, and phosphoric acid until the tetraethyl orthosilicate is completely dissolved. Then add polyvinyl alcohol aqueous solution and stir evenly to obtain Si sol. Perform electrospinning on the Si sol to obtain Si electrospun film. Calcine the Si electrospun film to obtain amorphous SiO2 nanofiber film.

[0006] Step 2: Au is deposited on the surface of the amorphous SiO2 nanofiber film obtained in Step 1 using ion sputtering;

[0007] Step 3: Place Sn powder at the bottom of a quartz tube with one open end, and put the amorphous SiO2 nanofiber membrane after Au plating in Step 2 into the quartz tube. Then, put the quartz tube into a tube furnace, introduce a mixed gas of oxygen and argon, and perform heat treatment under vacuum. After heat treatment, allow it to cool naturally to room temperature to obtain an all-inorganic flexible permeable SiO2@SnO2 needle-like fiber membrane gas-sensitive material.

[0008] In step 1 above, the thickness of the amorphous SiO2 nanofiber film is 0.1 to 1.5 mm.

[0009] In step 1 above, the mass ratio of distilled water, tetraethyl orthosilicate, phosphoric acid, and polyvinyl alcohol aqueous solution is 125:125-250:1-1.5:125-250; the mass fraction of the polyvinyl alcohol aqueous solution is 10%-16%; the electrospinning feed rate is 0.8-1.4 mL / h, the voltage is 18-24 kV, and the spinning time is 4-10 hours; the calcination temperature is 600-800℃, and the time is 2-5 hours.

[0010] In step 2 above, the time for depositing Au on the surface of the amorphous SiO2 nanofiber film using ion sputtering is 10 to 30 seconds.

[0011] In step 3 above, the diameter of the quartz tube is 20-30 mm and the length is 80-150 mm.

[0012] In step 3 above, the distance between the Au-plated amorphous SiO2 nanofiber film and the Sn powder is 10-60 mm.

[0013] In step 3 above, the flow rate of the oxygen and argon mixture is 50-300 mL / min, and the volume percentage of oxygen in the mixture is 0.05%-0.2%.

[0014] In step 3 above, the heating rate of the heat treatment is 5-30℃ / min, the temperature is 700-850℃, the time is 0.5-4 hours, and the vacuum degree in the tube furnace is 0.1-1kPa.

[0015] This invention utilizes SiO2 nanofibers, which possess excellent flexibility, heat resistance, and chemical inertness, as the substrate and framework material. Extremely fine SnO2 nanowires are grown on the surface of the SiO2 nanofibers using a CVD method, resulting in a fully inorganic, flexible, and breathable SiO2@SnO2 needle-like fiber membrane. Compared with existing technologies, the advantages of this invention are as follows:

[0016] 1. The SiO2@SnO2 pine needle-like fiber membrane of the present invention is composed of SiO2 nanofibers and SnO2 nanowires. The SiO2 nanofibers and SnO2 nanowires are interwoven to form a network structure. On the one hand, the SiO2 nanofibers, as a skeleton material, have good flexibility; on the other hand, the SnO2 nanowires grow densely on the surface of amorphous SiO2 nanofibers to form a hierarchical nanostructure similar to pine needles. Under bending conditions, the bending stress generated is mainly concentrated in the SiO2 fibers. At the bending interface, the SnO2 nanowires growing perpendicular to the interface only bear a small stress, while the SnO2 nanowires at the non-bending interface are almost unaffected by stress. Furthermore, the fine SnO2 nanowires can undergo slight deformation after being subjected to stress, avoiding stress concentration. In addition, the SnO2 nanowires in the fiber membrane have a finer diameter and better flexibility than SnO2 nanofibers. Therefore, the SiO2@SnO2 pine needle-like fiber membrane of the present invention exhibits good flexibility and structural stability.

[0017] 2. This invention grows dense SnO2 nanowires on the surface of SiO2 nanofibers. On the one hand, the SiO2 nanofibers, acting as a framework material, are wrapped by the SnO2 nanowires, which does not hinder the conductivity between the SnO2 nanowires, thus ensuring the electrical stability of the sensor. On the other hand, the pine needle-like SiO2@SnO2 intertwine to form a network structure, which can maintain a good intertwined state during bending, greatly enriching the contact interface between SnO2 and SiO2. This makes it less likely for SnO2 and SiO2 to separate during bending, thus ensuring the electrical stability of the fiber membrane sensor during bending deformation.

[0018] 3. The SiO2@SnO2 needle-like fiber membrane of the present invention exhibits good high temperature resistance and can maintain a stable structure below 800℃. This is partly due to the good high temperature resistance of SiO2 nanofibers and SnO2 nanowires, which do not undergo phase change at 800℃ and can maintain good flexibility. On the other hand, the two materials have similar coefficients of thermal expansion, which avoids cracking caused by the difference in the coefficients of thermal expansion of the two materials during high-temperature heat treatment.

[0019] 4. The SiO2@SnO2 needle-like fiber membrane of the present invention exhibits good air permeability. This is due to the three-dimensional network structure of the fiber membrane, which contains a large number of channels for molecular diffusion, providing channels for the diffusion of gas molecules in gas-sensitive testing.

[0020] 5. This invention fabricates a gas sensor by spraying electrodes onto the surface of a SiO2@SnO2 needle-like fiber membrane. This sensor exhibits excellent NO2 gas-sensing performance, achieving a response value of 703 for 200 ppb NO2 at room temperature. This represents a 614-fold improvement over SnO2 sensors prepared by electrospinning, and significantly shortens the recovery time. This is attributed to the porous structure of the fibers and the extremely fine particle size of the SnO2, which enhances the gas-sensing response. Furthermore, the sensor demonstrates good stability; the resistance change does not exceed 5% during cyclic bending, and the NO2 gas-sensing performance does not decay after 10,000 cycles of bending at 140°.

[0021] 6. The process parameters for preparing the all-inorganic flexible breathable SiO2@SnO2 pine needle-like fiber membrane gas-sensitive material of the present invention are well controllable, and it is easy to obtain products with stable performance. Attached Figure Description

[0022] Figure 1 This is a photograph of the SiO2@SnO2 pine needle-like fiber membrane prepared in Example 1 after being cut and in a bent state.

[0023] Figure 2 These are the X-ray diffraction patterns of the SiO2@SnO2 fiber membranes prepared in Example 1 and Comparative Examples 1-2.

[0024] Figure 3 These are SEM images of the SiO2@SnO2 fiber membranes prepared in Example 1 and Comparative Examples 1-2 at different magnifications.

[0025] Figure 4 These are TEM and HRTEM images of nanowires in the SiO2@SnO2 needle-like fiber membrane prepared in Example 1.

[0026] Figure 5 This is a SEM image of the SiO2@SnO2 pine needle-like fiber membrane prepared in Example 2.

[0027] Figure 6 This is a SEM image of the SiO2@SnO2 pine needle-like fiber membrane prepared in Example 3.

[0028] Figure 7 These are the response curves of SiO2@SnO2 fiber membranes from Examples 1 and Comparative Examples 1-2, as well as sensors prepared from ordinary SnO2, to different concentrations of NO2 at room temperature.

[0029] Figure 8 The curve shows the resistance change of the flexible gas sensor prepared by the SiO2@SnO2 pine needle fiber membrane in Example 1 during cyclic bending at 140°.

[0030] Figure 9This is the stress change curve of the flexible gas sensor prepared by the SiO2@SnO2 pine needle fiber membrane in Example 1 during cyclic bending at 140°.

[0031] Figure 10 The values ​​are the response values ​​of the flexible gas sensor prepared by the SiO2@SnO2 pine needle fiber membrane in Example 1 to 200ppb NO2 at different bending angles.

[0032] Figure 11 The values ​​are the response values ​​of the flexible gas sensor prepared from the SiO2@SnO2 pine needle fiber membrane in Example 1 to 200 ppb NO2 after different cycles of bending.

[0033] Figure 12 This is a radar image showing the response of the flexible gas sensor prepared from the SiO2@SnO2 pine needle-like fiber membrane of Example 1 to various gases at room temperature. Detailed Implementation

[0034] The present invention will now be described in detail with reference to the embodiments and accompanying drawings, but the scope of protection of the present invention is not limited to these embodiments.

[0035] Example 1

[0036] Step 1: Mix 10.0g distilled water, 10.0g tetraethyl orthosilicate, and 100mg phosphoric acid until the tetraethyl orthosilicate is completely dissolved. Then add 18.0g of 11% polyvinyl alcohol aqueous solution and stir until homogeneous to obtain Si sol. Perform single-needle electrospinning on the Si sol at a feed rate of 1.0mL / h and a voltage of 20kV for 4h to obtain a Si electrospun membrane. Calcinate the collected Si electrospun membrane at 650℃ for 3h to obtain an amorphous SiO2 nanofiber membrane with a thickness of approximately 0.8mm.

[0037] Step 2: Place the amorphous SiO2 nanofiber film into an ion sputtering device and sputter an Au film on the surface of the amorphous SiO2 nanofiber film for 20 seconds.

[0038] Step 3: Weigh 500 mg of Sn powder, pour it into the bottom of a quartz tube with one open end, a diameter of 25 mm and a length of 150 mm, place the Au-plated amorphous SiO₂ nanofiber membrane into the quartz tube at a distance of 20 mm from the Sn powder; then place the quartz tube in the center of a tube furnace, feed a mixed gas of oxygen and argon at a flow rate of 80 mL / min, wherein the volume fraction of oxygen in the mixed gas is 0.1%; turn on the vacuum pump supporting the tube furnace to keep the tube furnace in a vacuum state with a vacuum degree maintained at 0.5 kPa, start heating the tube furnace, raise the temperature to 800 °C at a rate of 30 °C / min, and keep the temperature for 2.5 h; after natural cooling to room temperature, the fully inorganic flexible breathable SiO₂@SnO₂ pine needle-shaped fibrous membrane gas-sensitive material is obtained.

[0039] Example 2

[0040] Step 1: Mix and stir 10.0 g of distilled water, 12 g of tetraethyl orthosilicate and 120 mg of phosphoric acid until the tetraethyl orthosilicate is completely dissolved, then add 17.0 g of a 12 wt% polyvinyl alcohol aqueous solution and stir uniformly to obtain a Si sol; perform single-needle electrostatic spinning on the Si sol at a propulsion rate of 1.0 mL / h and a voltage of 20 kV for 5 hours of spinning to obtain a Si electrospun membrane; calcinate the collected Si electrospun membrane at a calcination temperature of 800 °C for a holding time of 2 h to obtain an amorphous SiO₂ nanofiber membrane with a thickness of about 1.0 mm.

[0041] Step 2: Place the amorphous SiO₂ nanofiber membrane in an ion sputtering apparatus, and sputter a layer of Au film on the surface of the amorphous SiO₂ nanofiber membrane for a sputtering time of 30 s.

[0042] Step 3: Weigh 300 mg of Sn powder, pour it into the bottom of a quartz tube with one open end, a diameter of 20 mm and a length of 150 mm, place the Au-plated amorphous SiO₂ nanofiber membrane into the quartz tube at a distance of 20 mm from the Sn powder; then place the quartz tube in the center of a tube furnace, feed a mixed gas of oxygen and argon at a flow rate of 80 mL / min, wherein the volume fraction of oxygen in the mixed gas is 0.2%; turn on the vacuum pump supporting the tube furnace to keep the tube furnace in a vacuum state with a vacuum degree maintained at 0.5 kPa, start heating the tube furnace, raise the temperature to 800 °C at a rate of 20 °C / min, and keep the temperature for 1.5 h; after natural cooling to room temperature, the fully inorganic flexible breathable SiO₂@SnO₂ pine needle-shaped fibrous membrane gas-sensitive material is obtained.

[0043] Example 3

[0044] Step 1: Mix and stir 10.0 g of distilled water, 14.0 g of tetraethyl orthosilicate and 80.0 mg of phosphoric acid until tetraethyl orthosilicate is completely dissolved, then add 16.0 g of a 15 wt% polyvinyl alcohol aqueous solution and stir uniformly to obtain a Si sol; perform single-needle electrostatic spinning on the Si sol at a propulsion rate of 1.2 mL / h and a voltage of 20 kV for 6 h to obtain a Si electrospun fiber membrane; calcinate the collected Si electrospun fiber membrane at a calcination temperature of 700°C for a holding time of 2 h to obtain an amorphous SiO₂ nanofiber membrane with a thickness of about 1.3 mm.

[0045] Step 2: Place the amorphous SiO₂ nanofiber membrane in an ion sputtering apparatus, and sputter a layer of Au film on the surface of the amorphous SiO₂ nanofiber membrane for a sputtering time of 20 s.

[0046] Step 3: Weigh 750 mg of Sn powder, pour it into the bottom of a quartz tube with one end open, a diameter of 30 mm and a length of 150 mm, and place the Au-coated amorphous SiO₂ nanofiber membrane in the quartz tube at a distance of 40 mm from the Sn powder; then place the quartz tube in the center of a tube furnace, and feed a mixed gas of oxygen and argon at a flow rate of 200 mL / min, where the volume fraction of oxygen in the mixed gas is 0.05%; turn on the vacuum pump equipped with the tube furnace to keep the tube furnace under vacuum at a vacuum degree of 1 kPa, start heating the tube furnace, raise the temperature to 750°C at a rate of 30°C / min and hold for 1 h; after natural cooling to room temperature, the all-inorganic flexible breathable SiO₂@SnO₂ pine needle-like fiber membrane gas-sensitive material is obtained.

[0047] Comparative Example 1

[0048] The volume fraction of oxygen in the mixed gas described in Step 3 of Example 1 is changed to 0.25%, and the other steps are the same as those of Example 1 to obtain a SiO₂@SnO₂ fiber membrane gas-sensitive material.

[0049] Comparative Example 2

[0050] The volume fraction of oxygen in the mixed gas described in Step 3 of Example 1 is changed to 0.5%, and the other steps are the same as those of Example 1 to obtain a SiO₂@SnO₂ fiber membrane gas-sensitive material.

[0051] Figure 1 It is a photograph of the cut SiO₂@SnO₂ pine needle-like fiber membrane prepared in Example 1 in a bent state. In the bent state, the surface of the fiber membrane is intact without cracks, which indicates that the all-inorganic flexible breathable SiO₂@SnO₂ pine needle-like fiber membrane prepared in Example 1 has good flexibility.

[0052] Figure 2The X-ray diffraction patterns of the SiO2@SnO2 fiber membranes prepared in Examples 1 and Comparative Examples 1-2 are shown above. The XRD diffraction peaks of the three samples correspond well with the standard peaks numbered 41-1445, indicating that the fiber membranes prepared in Examples 1 and Comparative Examples 1-2 all contain SnO2. Since SiO2 nanofibers are amorphous, only one broadened diffraction peak appears near 22.2° in the X-ray diffraction pattern. Therefore, XRD indicates that the fiber membranes prepared in Examples 1 and Comparative Examples 1-2 are composed of SiO2 and SnO2.

[0053] Figure 3 The images show SEM images of the SiO2@SnO2 fiber membranes prepared in Example 1 and Comparative Examples 1-2. It can be seen that the membrane prepared in Example 1 has nanowires wrapped around the surface of SiO2 nanofibers, resembling a pine needle structure. After increasing the oxygen volume concentration in the mixed gas to 0.25%, a large number of ultra-long nanowires appeared on the surface of Comparative Example 1, covering the original SiO2 nanofibers. Further increasing the oxygen concentration to 0.5%, thicker nanowires appeared on the surface of Comparative Example 2, covering the original SiO2 nanofibers. Therefore, neither Comparative Example 1 nor Comparative Example 2 yielded a nanofiber membrane with a pine needle structure.

[0054] Figure 4 TEM images (a, b) and HRTEM image (c) at different magnifications of the SiO2@SnO2 needle-like fiber membrane prepared in Example 1 show that a large number of nanowires are coated on the surface of the SiO2 nanofibers. In the HRTEM image, the 0.264 nm crystal plane corresponds to the (101) crystal plane of SnO2, indicating that the nanowires coated on the surface of the SiO2 nanofibers in Example 1 are SnO2 nanowires. Therefore, Example 1 prepared a nanofiber membrane with SnO2 nanowires coated on the surface of SiO2 nanofibers, resembling a pine needle structure.

[0055] Figure 5 and Figure 6 The images show SEM images of the SiO2@SnO2 pine needle-like fiber membranes prepared in Examples 2 and 3, respectively. As can be seen from the images, SnO2 nanowires are wrapped on the surface of the SiO2 nanofibers, which indicates that SiO2@SnO2 nanofiber membranes with a similar pine needle structure were also prepared in Examples 2 and 3.

[0056] Figure 7The figures show the response values ​​of flexible gas sensors prepared using the SiO2@SnO2 pine needle-like fiber membrane in Example 1, the SiO2@SnO2 fiber membranes in Comparative Examples 1 and 2, and ordinary SnO2 to different concentrations of NO2 at room temperature. As can be seen from the figures, the flexible fiber membrane sensor prepared using the SiO2@SnO2 pine needle-like fiber membrane in Example 1 has a significantly higher response to NO2 than the sensors prepared using the SiO2@SnO2 fiber membranes in Comparative Examples 1 and 2 and ordinary SnO2. Specifically, the response value of the flexible gas sensor prepared using the SiO2@SnO2 pine needle-like fiber membrane in Example 1 to 200 ppb NO2 is more than 600 times that of the ordinary SnO2 sensor. This demonstrates that the flexible gas sensor prepared using the SiO2@SnO2 pine needle-like fiber membrane in Example 1 has the best room temperature NO2 gas sensing performance.

[0057] Figure 8 The resistance change curve of the flexible gas sensor prepared by the SiO2@SnO2 pine needle fiber membrane in Example 1 during cyclic bending of 140° shows that the resistance of the flexible gas sensor changes by 5% during bending, indicating that the sensor maintains good electrical stability during cyclic bending.

[0058] Figure 9 The figure shows the stress change curve of the flexible gas sensor prepared by the SiO2@SnO2 pine needle fiber membrane of Example 1 during cyclic bending of 140°. It can be seen from the figure that the external stress applied to the flexible gas sensor during the bending process from 0 to 140° is -18 to 0 mN, indicating that the flexible gas sensor prepared by the SiO2@SnO2 pine needle fiber membrane of Example 1 has good flexibility.

[0059] Figure 10 The figure shows the response values ​​of the flexible gas sensor prepared from the SiO2@SnO2 pine needle fiber membrane in Example 1 to 200ppb NO2 at different bending angles. As can be seen from the figure, the flexible gas sensor has good response stability to NO2 under different bending states. Figure 11 The figure shows the response of the flexible gas sensor prepared from the SiO2@SnO2 pine needle fiber membrane in Example 1 to 200ppb NO2 after different cycles of bending. As can be seen from the figure, the flexible gas sensor still maintains a stable response to NO2 after 10,000 cycles of bending. Figure 10 and Figure 11 This demonstrates that the gas sensor prepared from the SiO2@SnO2 pine needle-like fiber membrane in Example 1 exhibits good flexibility and NO2 gas sensing performance.

[0060] Figure 12The image shows a radar graph of the response of the flexible gas sensor prepared from the SiO2@SnO2 pine needle fiber membrane in Example 1 to various gases at room temperature. As can be seen from the graph, the response value of the flexible gas sensor to common gases is much lower than that to the lower concentration of NO2, indicating that the sensor has excellent selectivity for NO2 at room temperature.

[0061] comprehensive Figures 7-12 This indicates that the flexible gas sensor prepared from the SiO2@SnO2 needle-like fiber membrane in Example 1 exhibits good sensitivity, bending stability, and selectivity for NO2 at room temperature, which provides important support for its application in the field of flexible sensing.

Claims

1. A method for preparing a gas-sensitive material of all-inorganic flexible breathable SiO2@SnO2 pine needle-like fiber membrane, characterized in that, The preparation method includes the following steps: Step 1: Mix distilled water, tetraethyl orthosilicate, and phosphoric acid until the tetraethyl orthosilicate is completely dissolved. Then add polyvinyl alcohol aqueous solution and stir evenly to obtain Si sol. Perform electrospinning on the Si sol to obtain Si electrospun film. Calcine the Si electrospun film to obtain amorphous SiO2 nanofiber film. Step 2: Au is deposited on the surface of the amorphous SiO2 nanofiber film obtained in Step 1 using ion sputtering; Step 3: Place Sn powder at the bottom of a quartz tube with one open end, and place the amorphous SiO2 nanofiber membrane coated with Au in Step 2 into the quartz tube. Then, place the quartz tube into a tube furnace and introduce a mixed gas of oxygen and argon, wherein the volume percentage of oxygen in the mixed gas is 0.05% to 0.2%. Perform heat treatment under vacuum. After heat treatment, allow it to cool naturally to room temperature to obtain an all-inorganic flexible permeable SiO2@SnO2 needle-like fiber membrane gas-sensitive material.

2. The preparation method of the all-inorganic flexible breathable SiO2@SnO2 pine needle-like fiber membrane gas-sensitive material according to claim 1, characterized in that: In step 1, the thickness of the amorphous SiO2 nanofiber film is 0.1 to 1.5 mm.

3. The preparation method of the all-inorganic flexible breathable SiO2@SnO2 pine needle-like fiber membrane gas-sensitive material according to claim 1, characterized in that: In step 1, the mass ratio of distilled water, tetraethyl orthosilicate, phosphoric acid, and polyvinyl alcohol aqueous solution is 125:125-250:1-1.5:125-250; the mass fraction of the polyvinyl alcohol aqueous solution is 10%-16%; the electrospinning feed rate is 0.8-1.4 mL / h, the voltage is 18-24 kV, and the spinning time is 4-10 hours; the calcination temperature is 600-800 °C, and the time is 2-5 hours.

4. The preparation method of the all-inorganic flexible breathable SiO2@SnO2 pine needle-like fiber membrane gas-sensitive material according to claim 1, characterized in that: In step 2, the time for depositing Au on the surface of the amorphous SiO2 nanofiber film using ion sputtering is 10 to 30 seconds.

5. The preparation method of the all-inorganic flexible breathable SiO2@SnO2 pine needle-like fiber membrane gas-sensitive material according to claim 1, characterized in that: In step 3, the diameter of the quartz tube is 20-30 mm and the length is 80-150 mm.

6. The method for preparing the all-inorganic flexible breathable SiO2@SnO2 needle-like fiber membrane gas-sensitive material according to claim 1, characterized in that: In step 3, the distance between the Au-plated amorphous SiO2 nanofiber film and the Sn powder is 10–60 mm.

7. The preparation method of the all-inorganic flexible breathable SiO2@SnO2 pine needle-like fiber membrane gas-sensitive material according to claim 1, characterized in that: In step 3, the flow rate of the oxygen and argon mixture is 50–300 mL / min.

8. The method for preparing the all-inorganic flexible breathable SiO2@SnO2 needle-like fiber membrane gas-sensitive material according to claim 1, characterized in that: In step 3, the heating rate of the heat treatment is 5-30 °C / min, the temperature is 700-850 °C, the time is 0.5-4 hours, and the vacuum degree in the tube furnace is 0.1-1 kPa.

9. The all-inorganic flexible breathable SiO2@SnO2 needle-like fiber membrane gas-sensitive material obtained by any one of the preparation methods of claims 1 to 8.

Citation Information

Patent Citations

  • Flexible inorganic semiconductor resistance type room temperature gas sensor and preparation method thereof

    CN113325043A

  • ZnO-SnO_2 NANOFIBER-NANOWIRE STEM-BRANCH HETEROSTRUCTURE AND MANUFACTURING METHOD THEREOF, AND GAS SENSOR INCLUDING HETEROSTRUCTURE

    KR1020140139641A